Distinct functions and requirements for the Cys-His boxes of the human immunodeficiency virus type 1 nucleocapsid protein during RNA encapsidation and replication. - Schwartz, M D (1997)
The process of retroviral RNA encapsidation involves interaction between trans-acting viral proteins and cis-acting RNA elements. The encapsidation signal on human immunodeficiency virus type 1 (HIV-1) RNA is a multipartite structure composed of functional stem-loop structures. The nucleocapsid (NC) domain of the Gag polyprotein precursor contains two copies of a Cys-His box motif that have been demonstrated to be important in RNA encapsidation. To further characterize the role of the Cys-His boxes of the HIV-1 NC protein in RNA encapsidation, the relative efficiency of RNA encapsidation for virus particles that contained mutations within the Cys-His boxes was measured. Mutations that disrupted the first Cys-His box of the NC protein resulted in virus particles that encapsidated genomic RNA less efficiently and subgenomic RNA more efficiently than did wild-type virus. Mutations within the second Cys-His box did not significantly affect RNA encapsidation. In addition, a full complement of wild-type NC protein in virus particles is not required for efficient RNA encapsidation or virus replication. Finally, both Cys-His boxes of the NC protein play additional roles in virus replication.